Income redistribution in the European Union - EUROMOD; Avram, Silvia; Levy, Horacio; Sutherland, Holly (Colchester, 2014)
"The systems of direct taxes and cash benefits in the 27 Member States of the European Union (EU) vary considerably in size and structure. We explore their redistributive effects using EUROMOD, the tax-benefit microsimulation model for the EU. As well as describing redistributive effects in aggregate this allows us to assess and compare the effectiveness of individual types of policy in reducing income disparities. We consider the following categories of benefits and taxes: income taxes, tax allowances, tax credits, social contributions, cash benefits designed to target the poor or redistribute inter-personally (through means-testing) as well as cash benefits intended to redistribute intra-personally across the lifecycle (through social insurance or contingency-based entitlement). We derive results for the 27 members of the European Union using policies in effect in 2010 and present them for each country separately as well as for the EU as a whole."